Aqueous Extract of Red Deer Antler Promotes Hair Growth by Regulating the Hair Cycle and Cell Proliferation in Hair Follicles - Li, Jing-jie (Hindawi Publishing Corporation, 2014)
Deer antlers are the only mammalian appendage capable of regeneration. We aimed to investigate the effect of red deer antler extract in regulating hair growth, using a mouse model. The backs of male mice were shaved at eight weeks of age. Crude aqueous extracts of deer antler were prepared at either 4°C or 100°C and injected subcutaneously to two separate groups of mice (n = 9) at 1 mL/day for 10 consecutive days, with water as a vehicle control group. The mice skin quantitative hair growth parameters were measured and 5-bromo-2-deoxyuridine was used to identify label-retaining cells. We found that, in both the 4°C and the 100°C deer antler aqueous extract-injection groups, the anagen phase was extended, while the number of BrdU-incorporated cells was dramatically increased. These results indicate that deer antler aqueous extract promotes hair growth by extending the anagen phase and regulating cell proliferation in the hair follicle region.